Engaging underprivileged children in collaborative partnership via a curriculum - Muda, Suhaini (Elsevier Ltd., 2014)
Curriculum is one of the collaborative partnership strategies used in the community efforts to develop the underprivileged children in Malaysia.This curriculum was developed by the community members to assist community partnership efforts to impart ICT knowledge and skills, personal development elements, and encourage learners to contribute to the society via a CSP.Based on the available documents, this paper examines how the curriculum is able to bring the stakeholders together in the collaborative partnerships, and how underprivileged children are engaged in the efforts.This analysis will focus on the distinctive conjunction of personal development, ICT, and community service elements in the curriculum.